Cell-based screening identifies the active ingredients from Traditional Chinese Medicine formula Shixiao San as the inhibitors of atherosclerotic endothelial dysfunction. - Xiaofan Wang; Ruowen Zhang; Liqiang Gu; Yuanyuan Zhang; Xu Zhao; Kaishun Bi; Xiaohui Chen (PLoS ONE)
In this study, we performed a phenotypic screening in human endothelial cells exposed to oxidized low density lipoprotein (an in vitro model of atherosclerotic endothelial dysfunction) to identify the effective compounds in Shixiao San. After investigating the suitability and reliability of the cell-based screening method using atorvastatin as the positive control drug, this method was applied in screening Shixiao San and its extracts. The treatment of n-butanol fraction on endothelial cells exhibited stronger healing effects against oxidized low density lipoprotein-induced insult when compared with other fractions. Cell viability, the level of nitric oxide, endothelial nitric oxide synthase and endothelin-1 were measured, respectively. The assays revealed n-butanol fraction significantly elevated the survival ratio of impaired cells in culture. In parallel, n-butanol fraction exhibited the highest inhibition of inflammation. The generation of prostaglandin-2 and adhesion molecule (soluble intercellular adhesion molecule-1) was obviously declined. Furthermore, n-butanol fraction suppressed the production of reactive oxygen species and malondialdehyde, and restored the activity of superoxide dismutase. Compounds identification of the n-butanol fraction was carried out by ultra high liquid chromatography coupled to quadrupole time-of-flight tandem mass spectrometry. The active ingredients including quercetin-3-O-(2G-α-l-rhamnosyl)-rutinoside, quercetin-3-O-neohesperidoside, isorhamnetin-3-O-neohesperidoside and isorhamnetin-3-O-rutinoside revealed the ability of anti-atherosclerosis after exposing on endothelial cells. The current work illustrated the pharmacology effect of Shixiao San and clearly indicated the major active components in Shixiao San. More importantly, the proposed cell-based screening method might be particularly suitable for fast evaluating the anti-atherosclerosis efficacy of Traditional Chinese Medicines and screening out the interesting ingredients of Traditional Chinese Medicines.